Assessment of Social Assistant Competencies Standard on the Base of Social Work Systems - Hermawati, Istiana (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This This research is aimed to describe social companion profiles; identifying social companion qualifications and the amount of incentives received per month; describing competences of the social companion; describing the development of social companion competence standards, and formulating standard hypothetical models of social companion on the base of social work systems. The research was conducted in five locations involving 150 respondents that were determined by proportional random sampling technique and a number of informants that were determined purposively. The data are collected through questionnaires, in-depth interviews, FGD and documents. The data are then analyzed quantitatively and qualitatively, which are both used simultaneously. The results of the study indicate that: 1) The majority of female companions are in the range of productive age, in married status, relatively well educated, coming from the local area and on average accompanying 48 PMKS, 2) From companion qualification, only 28 percent of social companions are qualified as professional social workers, the majority of companions (as many as 67 percent) have never attended the training of consolidation as social companions, and 75.33 percent of social companions received incentives of less than Rp. 500.000, - per month. Many companions function to accompany several PMKS programs and because of the little amount of the incentive they received, consequently they are less focused and their performance is less optimal; 3). Based on testing of contract model of social companion competence with confirmatory factor analysis (CFA) technique, it can be concluded that the competence of social companion was successfully reflected by certain knowledge, skill and values /attitude variable. Among the three variables tested, the factor content of the skill variable is merely the highest in forming competence; 4) The recruitment system of companions is identified in three ways, namely: a) direct recruitment system; b) election system; c) appointment system; 5) Developing social companion standard on the base of social work system, can be created by optimizing various components in the system including recruitment system, human resource management system, intervention system and training system. This research recommends that it is urgently needed to decide the related legislation to national standard of social companion so that the position of the companion is growing stronger and its competence is standardized; it is necessary to increase the competence of social companion, either through formal and nonformal education channels and it is also necessary to apply a hypothetical model of development of social companion standards based on the social work system as proposed.